2020
DOI: 10.3171/2018.12.jns181578
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparisons of different hypofractionated stereotactic radiotherapy techniques in treating intracranial tumors > 3 cm in longest diameter

Abstract: OBJECTIVEThe authors sought to compare the dosimetric quality of hypofractionated stereotactic radiosurgery in treating sizeable brain tumors across the following treatment platforms: GammaKnife (GK) Icon, CyberKnife (CK) G4, volumetric modulated arc therapy (VMAT) on the Varian TrueBeam STx, double scattering proton therapy (DSPT) on the Mevion S250, and intensity modulated proton therapy (IMPT) on the Varian ProBeam.METHODSIn this retrospective study, stereotactic radiotherapy treatment plans were generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
1
28
2
1
Order By: Relevance
“…After an international meta-analysis of Lehrer et al in 2018, 17 studies across 15 institutes in 3 countries have been analyzed and shown that concurrent administration of immune checkpoint inhibitors and SRS does not appear to be associated with untoward rates of radionecrosis with a possible survival advantage observed. Additionally, enhanced regional brain control within the brain with excellent rates of 1-year LC may be associated with concurrent therapy [57,58]. This argues for non-invasive treatment of brain metastases even in advanced and extra-cranially spread disease to prevent progression and subsequent neurological deterioration, while treating the underlying disease effectively.…”
Section: Discussionmentioning
confidence: 99%
“…After an international meta-analysis of Lehrer et al in 2018, 17 studies across 15 institutes in 3 countries have been analyzed and shown that concurrent administration of immune checkpoint inhibitors and SRS does not appear to be associated with untoward rates of radionecrosis with a possible survival advantage observed. Additionally, enhanced regional brain control within the brain with excellent rates of 1-year LC may be associated with concurrent therapy [57,58]. This argues for non-invasive treatment of brain metastases even in advanced and extra-cranially spread disease to prevent progression and subsequent neurological deterioration, while treating the underlying disease effectively.…”
Section: Discussionmentioning
confidence: 99%
“…They were observed in the GI and V 3 Gy –V 24 Gy of normal brain tissue. Cao et al had compared dose metrics for six different plans. They found that the V 12 Gy of CK and GK plan was smaller than coplanar and non‐coplanar VMAT plans.…”
Section: Discussionmentioning
confidence: 99%
“…Beside conventional C‐arm based linear accelerator, there are some distinctive technologies, such as Gamma Knife (GK) and CyberKnife (CK). Due to non‐coplanar beams and the non isocentric nature of CK, the advantage of CK is quick dose falloff and better protection of normal brain tissue . CK contains a high‐resolution image‐guided tracking system to adjust the angle of beams during treatment to ensure the accuracy of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This variability may be especially pertinent when dealing with lesions near critical structures such as the brainstem or optic chiasm [5]. Such targets are usually best treated with a fractionated approach, which is now possible using MB GK SRS [21].…”
Section: Comparisons To Current Literaturementioning
confidence: 99%
“…As it currently stands, there is a gap in the literature comparing patient perspectives between SRS with a frame and SRS with a mask. The development of the Elekta Gamma Knife Icon in 2015 provided a unique opportunity to compare FB and MB SRS because the 2 can occur on the same treatment platform while maintaining the sharpest dose falloff gradient compared with other SRS treatment modalities [6,21]. The present study aims to analyze patient experiences of FB and MB SRS with respect to the comfort, pain, and perception of the procedure.…”
Section: Introductionmentioning
confidence: 99%